2013
DOI: 10.1063/1.4772975
|View full text |Cite
|
Sign up to set email alerts
|

Infrared light management in high-efficiency silicon heterojunction and rear-passivated solar cells

Abstract: Silicon heterojunction solar cells have record-high open-circuit voltages but suffer from reduced short-circuit currents due in large part to parasitic absorption in the amorphous silicon, transparent conductive oxide (TCO), and metal layers. We previously identified and quantified visible and ultraviolet parasitic absorption in heterojunctions; here, we extend the analysis to infrared light in heterojunction solar cells with efficiencies exceeding 20%. An extensive experimental investigation of the TCO layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
208
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 285 publications
(213 citation statements)
references
References 47 publications
4
208
0
1
Order By: Relevance
“…Consequently, if the dielectric layer is thin and has non-zero extinction, it will strongly absorb p-polarized light at high angles of incidence. We observed this in the rear TCO in silicon heterojunction solar cells; 11 it is also the principle behind metal overlayer-attenuated total reflection, an IR spectroscopic technique to enhance the absorption of ultrathin layers under investigation. 19,20 Most interesting for this study, F z (z) is near-zero at the metal surface; instead, F x (z), and to a lesser extent F y (z), is resonant with the metal.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, if the dielectric layer is thin and has non-zero extinction, it will strongly absorb p-polarized light at high angles of incidence. We observed this in the rear TCO in silicon heterojunction solar cells; 11 it is also the principle behind metal overlayer-attenuated total reflection, an IR spectroscopic technique to enhance the absorption of ultrathin layers under investigation. 19,20 Most interesting for this study, F z (z) is near-zero at the metal surface; instead, F x (z), and to a lesser extent F y (z), is resonant with the metal.…”
Section: Resultsmentioning
confidence: 98%
“…4,5 In a recent investigation of the TCO layers in amorphous silicon/crystalline silicon heterojunction solar cells, we confirmed this finding with both simulations and experiments, and demonstrated that J sc may be increased by 0.5 mA cm 22 with rear TCO layers that minimize the penetration of evanescent waves to the metallic reflector. 11 In this paper, we expose the physics of parasitic absorption in the metal of rear-passivated solar cells by calculating the electric field intensities in semiconductor/dielectric/metal structures. We then develop a simple formalism for predicting the rear internal reflectance and total IR reflectance of a solar cell given specific dielectric and metal layers, thereby facilitating the optimization of these layers.…”
Section: Introductionmentioning
confidence: 99%
“…[140] and ref. [141], respectively. The popularity of both TCOs for application as window layers in solar cells is partly due to their chemical and environmental stability, as well as their demonstrated largescale production.…”
Section: Progress Reportmentioning
confidence: 99%
“…To overcome this disadvantage and achieve high efficiencies, a transparent conductive oxide (TCO) layer is required on top of the emitter for lateral transport of photogenerated charge carriers to metal finger contacts; the TCO also serves as a single-layer antireflection coating. To reduce optical losses associated with free-carrier absorption in TCOs, 5 new high-mobility materials such as hydrogenated indium oxide are being introduced. [6][7][8] Another feature of the a-Si:H emitter is that it forms a heterojunction with c-Si due to their different bandgaps and electron affinities.…”
Section: Introductionmentioning
confidence: 99%